The handbook of journalism studies [electronic resource] - Hanitzsch, Thomas , 1969-; Wahl-Jorgensen, Karin (International Communication Association handbook series, 2009)
"This handbook charts the growing area of journalism studies, exploring the current state of theory and setting an agenda for future research in an international context. The volume is structured around theoretical and empirical approaches, and covers scholarship on news production and organizations; news content; journalism and society; and journalism in a global context." "Emphasizing comparative and global perspectives, each chapter explores: key elements, thinkers, and texts; historical context; current state-of-the-art; methodological issues; merits and advantages of the approach/area of studies; limitations and critical issues of the approach/area of studies; and directions for future research." "Offering broad international coverage from top-tier contributors, this volume ranks among the first publications to serve as a comprehensive resource addressing theory and scholarship in journalism studies. As such, The Handbook of Journalism Studies is a must-have resource for scholars and graduate students working in journalism, media studies, and communication around the globe."--Jacket.